2016
DOI: 10.1002/prot.25210
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage acidic protein 1, a new member of the beta-propeller protein family with amyloid propensity

Abstract: Cartilage acidic protein1 (CRTAC1) is an extracellular matrix protein of chondrogenic tissue in humans and its presence in bacteria indicate it is of ancient origin. Structural modeling of piscine CRTAC1 reveals it belongs to the large family of beta-propeller proteins that in mammals have been associated with diseases, including amyloid diseases such as Alzheimer's. In order to characterize the structure/function evolution of this new member of the beta-propeller family we exploited the unique characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…KLHL2 is a component of an ubiquitin-protein ligase complex that mediates the ubiquitination of target proteins, which most often leads to their proteasomal degradation and plays a role in the actin cytoskeleton reorganization. The CRTAC1 gene encodes a glycosylated extracellular matrix protein located in the interterritorial matrix of articular deep zone cartilage and the protein may be involved in cell-cell or cell-matrix interactions (Anjos et al, 2017 ). Overall, these examples provide strong evidence that the network methodology used in this study allows the co-localization of biologically relevant genes with a close relationship to different aspects of meat quality variation.…”
Section: Resultsmentioning
confidence: 99%
“…KLHL2 is a component of an ubiquitin-protein ligase complex that mediates the ubiquitination of target proteins, which most often leads to their proteasomal degradation and plays a role in the actin cytoskeleton reorganization. The CRTAC1 gene encodes a glycosylated extracellular matrix protein located in the interterritorial matrix of articular deep zone cartilage and the protein may be involved in cell-cell or cell-matrix interactions (Anjos et al, 2017 ). Overall, these examples provide strong evidence that the network methodology used in this study allows the co-localization of biologically relevant genes with a close relationship to different aspects of meat quality variation.…”
Section: Resultsmentioning
confidence: 99%
“…; Anjos et al . ). CRATC1 is a chondrocyte marker protein which has been used to differentiate cells with a chondroprogenitor and osteoprogenitor background (Grgurevic et al .…”
Section: Directional Cues Provided By Agismentioning
confidence: 97%
“…Cartilage acidic protein 1B (CRTAC1-B, LOTUS) is an alternatively spliced form of cartilage acidic protein-1 (CRTAC1) which is expressed exclusively in the CNS. CRTAC1 is a chondrocyte ECM protein member of a large family of evolutionary and phylogenetically conserved beta-propellor proteins (Redruello et al 2010;Anjos et al 2017). CRATC1 is a chondrocyte marker protein which has been used to differentiate cells with a chondroprogenitor and osteoprogenitor background (Grgurevic et al 2007;Steck et al 2007).…”
Section: Directional Cues Provided By Agismentioning
confidence: 99%
“…Enzymatic assays or flow cytometry have been used to assess active molecules for proliferative or apoptotic activities, qPCR can identify genes that regulate fibroblast migration/ECM production and electrical cell-substrate impedance sensing (ECIS) assays [6] give a direct measure of cell migration. CRTAC1 is an ECM protein that was first isolated from human chondrogenic tissue [7] and subsequently described in other vertebrates, non-vertebrate eukaryotes and in some prokaryotes [8,9]. Two splice variants of CRTAC1, with a widespread tissue distribution have been described in humans (a long form hCRTAC1-A and a short form, hCRTAC1-B) [7], which are of interest because of their association with a diversity of diseases of hard and soft tissue [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in mice that only possess Crtac1B, revealed that in the brain it is a key factor in lateral olfactory tract (LOT) formation, and it was named LOTUS (for LOT usher substance) [14] Crtac1B is also expressed by mice chondrocytes but gene deletion fails to cause an overt phenotype, although in an osteoarthritic model it significantly inhibited cartilage degradation, osteophyte formation and gait abnormalities in females [15]. Structural analysis and modeling of CRTAC1 suggests it may have several yet unexplored functions, it belongs to a family of β-propeller proteins that share several conserved motifs/domains [8,9,16]. The structure of CRTAC1 has been well conserved during its evolution; it has an N-terminal integrin α chain like-domain, an ASPIC/UnbV domain and a C-terminal calcium-binding epidermal growth factor domain (EGF-Ca).…”
Section: Introductionmentioning
confidence: 99%